Vision After Early-Onset Lesions of the Occipital Cortex: I. Neuropsychological and Psychophysical Studies - D. C. Kiper; P. Zesiger; P. Maeder; T. Deonna; G. M. Innocenti (Neural Plasticity)
We analyzed the visual functions of two patients (MS, FJ) with bilateral lesion of the primary visual cortex, which occurred at gestational age 33 wk in MS and at postnatal month 7 in FJ. In both patients basic visual functions— visual acuity, contrast sensitivity, color, form, motion perception—are similarly preserved or modestly impaired. Functions requiring higher visual processing, particularly figure-ground segregation based on textural cues, are severely impaired. In MS, studied longitudinally, the deficits attenuated between the ages of 4.5 and 8 y, suggesting that the developing visual system can display a considerable degree of adaptive plasticity several years after the occurrence of a lesion. In FJ (age 18:9 to 20:6 y), who is more impaired, the recovery, if any, was less.